Factors Affecting Anxiety Levels in Pre-Cataract Surgery Patients - TATA MAHYUVI (Politeknik Karya Husada, 2023)
ABSTRACT Introduction. Surgery is an experience that can cause anxiety. Anxiety arises as a result of an individual's psychological reactions, and excessive internal and external stimuli or stimuli have an impact on the inability to handle it. Perioperative anxiety in cataract surgery affects the majority of patients, fear of death dominates the patient's concern regardless of whether the patient underwent surgery. Objective: The aim of this study was to analyze the relationship between characteristics (age, gender, education, and experience) with the level of anxiety of patients undergoing surgical procedures cataract at Bhakti Mulia Hospital Jakarta. Methods: the research method used was descriptive correlational analytic with a cross-sectional approach. The number of samples was 72 respondents with a non-probability sampling technique, namely quota sampling. The statistical test used was the Spearman Rank. Results:The results showed that there was a significant correlation of 0.006 with a closeness level of 0.320 between age and anxiety level. There is a significant relationship of 0.000 with a closeness level of -478 between the level of education and the level of anxiety. There is a significant relationship of 0.000 with a closeness level of 0.513 between experience and anxiety levels. Meanwhile, gender characteristics do not show a significant relationship with the level of anxiety with a p-value of 0.515, a closeness level of -0.078. 000 with a closeness level of -478 between the level of education and the level of anxiety. There is a significant relationship of 0.000 with a closeness level of 0.513 between experience and anxiety levels. Meanwhile, gender characteristics do not show a significant relationship with the level of anxiety with a p-value of 0.515, a closeness level of -0.078. 000 with a closeness level of -478 between the level of education and the level of anxiety. There is a significant relationship of 0.000 with a closeness level of 0.513 between experience and anxiety levels. Meanwhile, gender characteristics do not show a significant relationship with the level of anxiety with a p-value of 0.515, a closeness level of -0.078. Keywords: Pre surgery patient, cataract, anxiety level